Understanding white-collar crime: a convenience perspective - Gottschalk, Petter (CRC Press, Taylor & Francis Group, 2017)
Chapter 1. Convenience theory of white-collar crime -- Chapter 2. Economical dimension in convenience theory -- Chapter 3. Organizational dimension in convenience theory -- Chapter 4. Behavioral dimension in convenience theory -- Chapter 5. Integrated approach to convenience theory -- Chapter 6. Empirical study of white-collar criminals -- Chapter 7. Statements for testing convenience hypotheses -- Chapter 8. Corporate social responsibility -- Chapter 9. Internal white-collar crime investigations -- Chapter 10. The case of the Betanien investigation.